New tool for greenhouse gas calculation tailored for cropland - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
SECTOR is ready to use. It is downloadable in the form of templates that can be used to develop custom versions with varying levels of dis-aggregated data entries at different scales. It is easily be adjusted to incorporate new emission factors and calculation procedures.